Demand or ideation? Evidence from the Iranian marital fertility decline. - Raftery, Adrian E.; Lewis, Steven M.; Aghajanian, Akbar (Demography, 1995)
A study was conducted, using data on fertility in Iran, to examine whether the onset of fertility decline is caused by structural socioeconomic changes or by the transmission of new ideas. The findings revealed that marital fertility in Iran began to decline in 1959, a few years after the beginning of huge economic growth around 1955, and that this decline continued until 1977. Over a quarter of the decline was found to be attributed to the reduction in child mortality, which is a central mechanism of demand theory. No evidence was found that the Family Planning Program or the Family Protection Act, which were both instituted in 1967, accelerated the fertility decline. Certainly neither caused the onset of the decline, which is what ideation theory would suggest. It appears that the Iranian fertility decline can be described more accurately by demand than by ideation theories. Other results that support this conclusion are discussed.